Microiontophoretic Application of Dynorphin in Dental Pain: Excitatory or Inhibitory Effects - Choi SH; Kim YM; Son JY; Ahn DK (Journal of Pain Research, 2025)
Seung-Ho Choi,* Yu-Mi Kim,* Jo-Young Son, Dong-Kuk Ahn Department of Oral Physiology, School of Dentistry, Kyungpook National University, Daegu, Korea*These authors contributed equally to this workCorrespondence: Dong-Kuk Ahn, Department of Oral Physiology, School of Dentistry, Kyungpook National University, 2177, Dalgubeol-Daero, Jung-Gu, Daegu, 41940, Korea, Tel +82-53-660-6840, Email dkahn@knu.ac.krBackground: The tooth exhibits increased sensitivity to noxious stimuli due to the dense innervation of thin myelinated Aδ fibers and unmyelinated C fibers within the dental pulp. While prior research has identified dynorphin expression in layers I–II of the dorsal horn across the spinal cord in various pain models, its functional role in trigeminal nociception, including tooth pain, remains underexplored. This study examines the potential role of dynorphin in the nociceptive processing of dental stimuli.Methods: Experiments were performed on adult male ferrets weighing 0.9– 1.4 kg. The effects of dynorphin on electrically evoked responses of tooth pulp neurons were recorded extracellularly.Results: The results demonstrated that the microiontophoretic application of dynorphin A induced excitatory and inhibitory effects on N-methyl-D-aspartate (NMDA)-evoked responses in electrically stimulated tooth pulp neurons. Specifically, dynorphin A attenuated NMDA-evoked responses in 16 out of 32 neurons by 61 ± 6%, facilitated NMDA-evoked responses in 10 out of 32 neurons by 69 ± 17%, and elicited mixed inhibitory and facilitatory responses in six out of 32 neurons. The inhibitory effects of dynorphin were blocked by nor-binaltorphimine, a kappa receptor antagonist, whereas the facilitatory effects were inhibited by D,L-2-amino-5-phosphonovaleric acid, an NMDA receptor antagonist.Conclusion: These findings suggest that dynorphin A-induced excitatory responses are mediated by NMDA receptors, whereas its inhibitory responses are mediated through kappa opioid receptors in dental pain. Thus, dynorphin exerts diverse effects, highlighting its role in the perception and modulation of dental pain.Keywords: dynorphin, N-methyl-D-aspartate, kappa receptor, dental pulp, analgesics